Transcriptomic Correlates of Immunologic Activation in Head and Neck and Cervical Cancer - Saiz-Ladera, Cristina; Baliu-Piqué, Mariona; Cimas, Francisco J.; Manzano, Aránzazu; García-Barberán, Vanesa; Camarero, Santiago Cabezas; Hinojal, Gonzalo Fernández; Pandiella, Atanasio; Győrffy, Balázs; Stewart, David; Cruz-Hernández, Juan J.; Pérez-Segura, Pedro; et al. (Frontiers in Oncology, 2021)
Targeting the immune system has emerged as an effective therapeutic strategy for the treatment of various tumor types, including Head and Neck Squamous Cell Carcinoma (HNSCC) and Non-small-Cell Lung Cancer (NSCLC), and checkpoint inhibitors have shown to improve patient survival in these tumor types. Unfortunately, not all cancers respond to these agents, making it necessary to identify responsive tumors. Several biomarkers of response have been described and clinically tested. As of yet what seems to be clear is that a pre-activation state of the immune system is necessary for these agents to be efficient. In this study, using established transcriptomic signatures, we identified a group of gene combination associated with favorable outcome in HNSCC linked to a higher presence of immune effector cells. CD2, CD3D, CD3E, and CXCR6 combined gene expression is associated with improved outcome of HNSCC patients and an increase of infiltrating immune effector cells. This new signature also identifies a subset of cervical squamous cell carcinoma (CSCC) patients with favorable prognosis, who show an increased presence of immune effector cells in the tumor, which outcome shows similarities with the HP-positive HNSCC cohort of patients. In addition, CD2, CD3D, CD3E, and CXCR6 signature is able to predict the best favorable prognosis in terms of overall survival of CSSC patients. Of note, these findings were not reproduced in other squamous cell carcinomas like esophageal SCC or lung SCC. Prospective confirmatory studies should be employed to validate these findings.